2012
DOI: 10.3109/08958378.2012.697494
|View full text |Cite
|
Sign up to set email alerts
|

Impacts after inhalation of nano- and fine-sized titanium dioxide particles: morphological changes, translocation within the rat lung, and evaluation of particle deposition using the relative deposition index

Abstract: A 3-week inhalation study with nano- and fine-sized titanium dioxide (TiO(2)) with 3, 28, and 90 days recovery time was performed in female Wistar rats. Lung volume measurements, histology, electron microscopy, hematology, and bronchoalveolar lavage (BAL) fluid analyses were conducted and the relative deposition index (RDI) was calculated. Minimal inflammatory changes in the lungs, leucopenia, and a decrease in β-glucuronidase were observed. Particles were mainly deposited in alveolar macrophages and, to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…Van Ravenzwaay et al also reported nano-TiO 2 (14% rutile, 86% anatase) accumulation in lymphoid tissue after inhalation exposure in the rat [20]. These results indicated that inhaled nano-TiO 2 could translocate throughout the body quickly and tend to accumulate in immune organ, which possibly through uptake by migratory antigen presenting cells, because many toxicological studies have observed that macrophages or foreign-body giant cells appeared in lung tissue as exposure doses increased [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…Van Ravenzwaay et al also reported nano-TiO 2 (14% rutile, 86% anatase) accumulation in lymphoid tissue after inhalation exposure in the rat [20]. These results indicated that inhaled nano-TiO 2 could translocate throughout the body quickly and tend to accumulate in immune organ, which possibly through uptake by migratory antigen presenting cells, because many toxicological studies have observed that macrophages or foreign-body giant cells appeared in lung tissue as exposure doses increased [21,22]. …”
Section: Discussionmentioning
confidence: 99%
“…For the nanoparticle pair TiO 2 P25 and TiO 2 T805, a 0.15 w-% phosphate buffer was chosen that had been successfully used in a nose-only experiment in rats to generate a partially nanoscaled TiO 2 P25 aerosol (Creutzenberg et al, 2009;Eydner et al, 2012). In case of TiO 2 T805 (hydrophobic surface properties because of surface-treatment with organics) Tween® 80 was used as an additional detergent auxiliary (Table 2).…”
Section: Preparation Of Particle Suspensionsmentioning
confidence: 99%
“…reported that exposure to TiO 2 by intraperitoneal injection induced obvious congestion and lymph nodule proliferation in the mouse spleen [61]. These results indicated that exposure to TiO 2 particles could translocate throughout the body quickly and tend to accumulate in immune organs, possibly through uptake by migratory antigen presenting cells, because many toxicological studies have observed that macrophages or foreign-body giant cells appeared in lung tissue as exposure doses increased [62]. …”
Section: Discussionmentioning
confidence: 99%